A Drosophila ecdysone-deficient model to assess the endocrine disruptor activity of Bisphenol A. - Vega-Cuesta, P.; Pulido, D.; Abia, D.; Herrera, S.; Lopez-Varea, A.; Ruiz-Gómez, A.; Fernández-Freire, P.; Peropadre, A.; de Celis, J.F. (Ecotoxicology and Environmental Safety, 2025)
Bisphenol A (BPA) is a well characterized endocrine disruptor that interferes with the activity of a variety of nuclear receptors. For this reason, BPA has the potential to impact the function of the endocrine system and alter cellular physiology. In this study, we present a novel experimental system to characterize the actions of dietary BPA on organism physiology. We used Drosophila melanogaster larvae genetically deficient for the synthesis of the major insect steroid hormone, ecdysone. These larvae exhibit a variety of phenotypes that can be rescued by dietary supplementation of 20-hydroxy-ecdysone or Ponasterone A, a naturally occurring ecdysteroid. We tested the effect of different concentrations of BPA exposure in this genetic background, and found that this chemical partially rescues the deficit in ecdysone. Furthermore, through in silico structural predictions of the Ecdysone receptor's ligand binding domain, we identified a protein domain capable of accommodating with different affinities ecdysone, Ponasterone A and BPA molecules. These findings pave the way for novel experimental approaches to identify and characterize new potential vertebrate endocrine disruptors.